1997
DOI: 10.1007/s003300050145
|View full text |Cite
|
Sign up to set email alerts
|

Determination of normal splenic volume on computed tomography in relation to age, gender and body habitus

Abstract: The purpose of our study was to examine variations in normal splenic size in relation to age, gender and body habitus in vivo, and to determine normative data for splenic volume on CT. The width (W), length (L), thickness (Th), cross-sectional areas and volume (Vol) of the spleen were obtained from abdominal CT examinations of 140 patients who underwent CT for indications unrelated to splenic disease. Splenic volume did not vary significantly (-0.04 < r < 0.05, p > 0.10) with the patient's age, gender, height,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
164
2
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(182 citation statements)
references
References 11 publications
12
164
2
4
Order By: Relevance
“…In MMM, however, the spleen size and weight can reach enormous proportions, with the weight often exceeding 7 kg [17]. In our patient, the estimated weight of the spleen was greater than 5 kg as calculated by CT measurements [18]. The massively enlarged spleen in conjunction with the hepatomegaly caused the increased IAP.…”
Section: Discussionmentioning
confidence: 65%
“…In MMM, however, the spleen size and weight can reach enormous proportions, with the weight often exceeding 7 kg [17]. In our patient, the estimated weight of the spleen was greater than 5 kg as calculated by CT measurements [18]. The massively enlarged spleen in conjunction with the hepatomegaly caused the increased IAP.…”
Section: Discussionmentioning
confidence: 65%
“…But, on average it is 2.5 cm thick, 7.5 cm wide and 12.5 cm long. [4] A sonographic study of adult spleen showed that spleen size decreased with increasing age. And, as it is reported from autopsy findings, the size of spleen was smaller in females than male study subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Congestive heart failure with ascites and hepatosplenomegaly, lymphoid tissue and haematological malignancies, glycogen storage disorders, sarcoidosis and amyloidosis are other important causes of splenic involvement. [3][4][5] The splenic parenchyma consists of lymphatic follicles and reticuloendothelial cells, surrounding the arteries ('white pulp') and an interspersed network of vascular sinusoids ('red pulp'). [3] The ratio of white to red pulp increases with age due to accumulated antigenic exposure and stimulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Litertatürde dalak hacmi üzerine yapılmış çok sayıda ça-lışma mevcuttur (8,(12)(13)(14)(15). Bu durum dalak hacminin doğru tespit edilmesine ve normal sınırlarının belirlenmesine yönelik gerekliliği ortaya koymaktadır.…”
Section: Discussionunclassified